Determinants of economic growth in Arab Countries: An Empirical Study compared with South-east Asia - ابراهيم, ابراهيم اديب (Journal of Economics and Administrative Sciences, 2013)
The study addresses the problem of stagnation and declining economic growth rates in Arab countries since the eighties till today after the progress made by these countries in the sixties of the last century. The study reviews the economic growth picture in Arab countries since the sixties to 2007. It also presents the views of some Applied Studies in regard to the relationship between economic growth and its factors (represented mainly by physical and human capitals) in Arab countries in reference to the reasons which responsible for that relationship.The  study addresses the impact of economic reform programs undertaken by  some of Arab countries on the economic growth rates, then conducts a statistical analysis on the growth factors effect in increasing the economic output per worker in both Arab  and South East Asia countries, for the period 1960-2005. The study ends with a set of conclusions and recommendations on how to overcome the crisis experienced by the economic growth in Arab countries in general.